PERAN MOTIVASI DAN KEPEMIMPINAN DALAM MENINGKATKAN PRESTASI KERJA KERJA KARYAWAN - Salju Salju (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2023)
Employee performance is an important element in the success and growth of the organization. Employee performance can be measured through various factors that reflect their contribution to the organization. Motivation and leadership are the two main factors that have a significant influence on employee performance. The combination of high motivation and effective leadership can have a positive impact on employee performance. Motivation provides intrinsic and extrinsic drives for employees to perform well, while leadership provides guidance, support, and inspiration to achieve the desired results. The purpose of this study is to determine the effect of motivation and leadership on employee performance. Determining the number of samples used in this study is done using the census method, where the total population of 45 employees is also used as a sample. The data analysis method used is multiple linear regression analysis. Based on the results of the analysis, it appears that motivation has a significant effect on employee performance. Meanwhile, the leadership variable has no significant effect on employee performance.